PENGARUH GINI RATIO, PENGELUARAN NON MAKANAN PER KAPITA, BELANJA DAERAH DAN LAJU PERTUMBUHAN EKONOMI PADA INDEKS PEMBANGUNAN MANUSIA KABUPATEN/KOTA DI PROVINSI BALI PERIODE 2004-2012 - Rustariyuni, Surya Dewi (PIRAMIDA; Vol 10 No 1 (2014): Jurnal PIRAMIDA, 2014)
United Nations Development Programme (UNDP) make a decision a priority message contain for every human development report start from whole level, national level or region level, there are development centered of human, position human as the last purpose from development, and not be a tool for development. UNDP make a decision for an index as measurement development increase that more good and all round than single size development increase growth PDRB per capita as knows with Human Development Index (HDI). HDI measure for the average result for a country in three dimention human development. The HDI region/city in Bali Province, there are increase result from 2004-2012 period. The aim of this research is to know influence variable gini ratio, expense non food per capita, region expenditure, and growth economy ratio to human development index in all region/city at Bali Province 2004-2012 period in a simultaneous or partial. The data used is secondary data from Center of Statistic Bureau of Bali Province. The analysis method is Pooled Least Square method with panel data. The result is for simultaneous all variable there are gini ratio, expense non food per capita, region expenditure, and growth economy ratio influential directly to human development index at nine region/city in Bali Province. Partially all variable are positive and significance to human development index. The positive influence of all variable, that have meaning if the government should do the even distribution development for all region in Province of Bali for keep the human development index and have increase result for all region. The Good Governance, with involce society and private as partner as long as realization of development also transparecny in government area that will be keep on the result human index development for all region in Bali.
Keywords: human development index,gini ratio,economic growth